Self-regulated learning in higher education: strategies adopted by computer programming students when supported by the SimProgramming approach - Pedrosa, Daniela (2017)
The goal of the SimProgramming approach is to help students overcome their learning difficulties in the transition from entry-level to advanced computer programming, developing an appropriate set of learning strategies. We implemented it at the University of Trás-os-Montes e Alto Douro (Portugal), in two courses (PM3 and PM4) of the bachelor programmes in Informatics Engineering and ICT. We conducted semi-structured interviews with students (n=38) at the end of the courses, to identify the students’ strategies for self-regulation of learning in the assignment. We found that students changed some of their strategies from one course edition to the following one and that changes are related to the SimProgramming approach. We believe that changes to the educational approach were appropriate to support the assignment goals. We recommend applying the SimProgramming approach in other educational contexts, to improve educational practices by including techniques to help students in their learning.